The Instability of Meaning: Deconstructing Visual Beauty in Seno Gumira’s “Gubrak!” - Wardani, Diah Ayu; Noor, Redyanto; Suryadi, Muhammad; Widyatwati, Ken (POETIKA, 2025)
This study examines the representation of female beauty in Seno Gumira Ajidarma’s short story Gubrak! through Jacques Derrida’s deconstruction approach. The short story tells the story of a woman with extraordinary beauty who causes mass panic, social chaos, and the destruction of the city. The main character experiences psychological burdens and alienation due to excessive social judgment of her physical appearance. The main issue examined is how the short story deconstructs conventional standards of beauty that have been legitimized by patriarchal views and visual culture. Using Jacques Derrida’s theory of deconstruction, this study examines how the text shakes the stable meaning of “beautiful” attached to women’s bodies based on the binary oppositions. The method used is qualitative descriptive analysis with deconstructive reading techniques. The analysis was conducted by identifying linguistic, narrative, and symbolic signs that indicate the instability of the meaning of “beautiful.” The results of the analysis show that beauty in the short story Gubrak! is not presented as a symbol of glory or happiness, but rather as a source of suffering and destruction. The meaning of “beautiful” in this text is not fixed and essential, but rather full of differences and contradictions. Excessive beauty causes alienation, social burdens, and collective chaos, thereby challenging patriarchal assumptions that worship physical beauty as a measure of a woman’s value. Thus, Gubrak! represents a critique of visual cultural constructs that reduce women to objects of gaze and affirms the function of literature as a space of resistance against the domination of singular meanings.